The Impact of Product Position and Packaging Shape on Consumers’ Preferences in Online Purchases. Moderating the Role of Faith in Buying Intuition - Wanat , Tomasz (Studia Oeconomica Posnaniensia, 2017)
The rules governing online merchandising differ from the rules of brick and mortar retail merchandising. These differences are partially related to the way products are presented in online stores. One of the main characteristics of online product presentation is the lack of realism in the products shape presentation. The goal of the article was to study the impact of product position in a set of products and the realism of products shape proportion on consumers’ preferences in online retail environments. The results of a laboratory experiment on a sample of 326 subjects indicate that the position of a product and shape proportions have a significant influence on consumers’ preferences but only in a group of consumers which are characterised by a low faith in buying intuition. In this group the recency effect and cheaper-and-smaller products effect have been observed.